Pharmaceuticals and personal care products in soil: Sources, impacts and myco-remediation strategies - Moharana Choudhury; Manab Deb Adhikari; Sangita Agarwal; Palas Samanta; Anu Sharma; Debajyoti Kundu; Sunil Kumar (Emerging Contaminants, 2025)
Bioremediation is an effective and sustainable method for removing xenobiotic pollutants from the environment, utilizing microorganisms and plants to metabolize harmful chemicals into harmless compounds like CO2 and water. Among various bioremediation strategies, mycoremediation stands out due to the unique enzymatic capabilities and metabolic diversity of fungi, enabling them to degrade persistent and toxic pollutants under harsh environmental conditions. This review specifically addresses the application of mycoremediation to emerging contaminants pharmaceuticals and personal care products (PPCPs) which pose significant environmental challenges due to their persistence, bioaccumulation potential, and ecotoxicity.This article provides a comprehensive overview of fungal-based strategies for PPCP remediation, documenting the fate, distribution, and impacts of these contaminants in soil. It highlights the enzymatic mechanisms and fungal species involved in PPCP degradation, with an emphasis on their ecological resilience and pollutant-specific adaptability. Additionally, the review explores under-discussed factors influencing fungal efficacy, such as pH, temperature, and contaminant concentration, alongside innovative advancements like myco-nanotechnology and enzyme engineering that enhance remediation efficiency.By integrating these aspects with policy perspectives and sustainable development goals, this review contributes novel insights into the potential of mycoremediation as a cutting-edge approach for mitigating PPCP contamination. It underscores the role of fungi in advancing circular economy principles and offers a foundation for future research and practical applications in environmental management.